(untitled) (Bangladesh Journal of Agricultural Research, 2008)
A study was conducted from June to December 2003 to assess weed dynamics and yield performance of transplanted aman rice (cv. BRRI Dhan39) in different weed control treatments e.g. two hand weedings at 15 and 40 DAT; Weeding by BRRI Weeder at 20 and 40 DAT; Rifit 500EC @ 1L/ha at 7 DAT; Rifit 500EC @ 1 L/ha at 7 DAT and one hand weeding at 40 DAT; Butachlor 5G @ 2 kg/ha at 7 DAT; Butachlor 5G @ 2 kg/ha at 7 DAT and one hand weeding at 40 DAT along with weed free and unweeded check under both good and poor water management practices. Weed density, weed biomass and weed control efficiency were significantly influenced by different weed control treatments under both water management practices. Other than weed free treatment, Butachlor 5G @ 2 kg/ha applied at 7 DAT along with one hand weeding at 40 DAT showed the best performance under good water management with minimum weed density (16 g/m2) as well as weed biomass (9.27 g/m2) and the highest weed control efficiency (82.57%). Yield and yield components were also significantly influenced by different weed control treatments and water management. The highest grain yield (5.22 t/ha) was obtained under good water management in weed free treatment followed by Butachlor 5G @ 2 kg/ ha and one hand weeding (4.96 t/ha) under same water management. Results revealed that integration of approaches, particularly Butachlor application along with one manual weeding accompanied by proper water management might be the best option to combat weed problems as well as to obtain satisfactory grain yield in transplanted aman rice. Key Words: Transplanted aman rice, water management, weed control treatment and yield. doi:10.3329/bjar.v33i3.1599 Bangladesh J. Agril. Res. 33(3) : 399-408, September 2008